PENGARUH FAKTOR KECERDASAN, KEPRIBADIAN DAN KAPASITAS KERJA TERHADAP PERFORMANSI DALAM TUGAS BERGANDA - , NI MADE SWASTI WULANYANI, Dr. Rahmat Hidayat, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Multitasking is defined as conducting several tasks simultaneously. There are three characteristics of multitasking. First, multitasking has circular characteristic and demand the performance of several tasks. Second, there is a shift of attention from one task to another. Third, the performance happens in limited time. Many companies apply multitasking to make their human resources more effective and efficient. If this proficiency can be predicted, companies will be able to reduce their expenses by appropriate selection or potential review to their human resources. Therefore, this study attempted to create the measurement methods of multitasking performance, to develop theoretical formulations by intelligence, personality, and work capacity factors, and to examine whether psychological tests could predict the multitasking proficiency. This study involved 324 undergraduate students of Udayana University-Bali who were in the sixth semester in 2012. The intelligence, personality and work capability of the subjects were measured by the IST (Intelligenz Struktur Test) 2000, 5th edition of 16 PF questionnaire and Kraeppelin test. The methodology used to measure the performance of multitasking was the computerized simulation of multitasking. The result show that subjects experienced 83.6% aspects of multitasking situation during the simulation. The result of regression analysis showed that General intelligence, Liveliness, Sensitivity, Rule consciousness, Apprehension personality traits and the Work Speed were the factors that have significant effect to the multitasking performance (RÂ²=0,339). Items on the analogy, number series, matrices, and verbal memory subtest of IST measurement